SINGLE NUCLEOTIDE POLYMORPHISMS WITHIN GENES REGULATING IMMUNE RESPONSE AND ANTIOXIDANT DEFENCE IN PATIENTS WITH COLORECTAL AND GASTRIC CANCER - Падюкова, Асия Дамировна; Южалин, Арсений Евгеньевич; Кутихин, Антон Геннадьевич; Волков, Алексей Николаевич; Попова, Юлия Александровна; Животовский, Алексей Станиславович; Магарилл, Юрий Абрамович; Цитко, Евгений Анатольевич; Брусина, Елена Борисовна (Medicine in Kuzbass, 2017)
Background. During the recent decade, studies on inherited variation within innate immune response and antioxidant defense genes and cancer highlighted a number of significant associations; however, this is not the case for colorectal cancer.Aim.  ofIL1B_1473G/C (rs1143623), SOD1_7958A/G (rs4998557), TLR4_1196C/T (rs4986791), IL10_1082A/G (rs1800896), IL17A_197G/A (rs2275913), andTLR4_896A/G (rs4986790) polymorphisms with colorectal and gastric cancer.Materials and methods. We recruited 244 consecutive patients with colorectal cancer and 72 patients with gastric canceralong with 300 age- and gender-matched asymptomatic individuals. Genotyping was carried out using allele-specific polymerasechain reaction following electrophoretic detection. Statistical analysis was performed bySNPStats software.Results. We revealed that heterozygous genotypes of theIL1B_1473G/C and TLR4_896A/G polymorphisms were significantly associated with a higher risk of colorectal cancer, particularly rectal cancer. Incontrast, C/Cgenotypeof the IL1B_1473G/C polymorphism was significantly associated with a lower risk of colon cancer.Conclusion. Polymorphisms within the genes encoding interleukins and Toll-like receptors may play a role in the development of colorectal cancer.
Keywords: colorectalcancer; gastriccancer; genes; polymorphisms; genetic risk factors